Trends in Computational Thinking Research in Science Education: A Systematic Review - Siti Nurazizah; Dwifta Fuji Maharani; Indah Juwita Sari; Jun S. Camara (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to investigate patterns in the application of computational thinking (CT) in scientific education. This study used a systematic review. Eleven papers from the ERIC database that were published between 2021 and 2025 were analyzed using the qualitative descriptive method. According to the review's findings, CT has been extensively employed across a range of educational levels, most notably in scientific and physics courses, as well as at the elementary school and high school levels. STEM is the most often utilized technique. CT has been used extensively in education and has been shown to improve student learning results, scientific idea comprehension, and critical thinking abilities.